Utilisation of Backscattered Gamma Photons in Tc-99m SPECT Imaging - Sayed, Inayatullah Shah; Leeman, Sidney; Tonge, Christine M (Pakistan Atomic Energy Commission, Islamabad, 1998)
A number of report have suggested that some Comptom-scattered gamma-photons do carry true spatial information even after multiple deflections in the imaged object, and scattered data have been used for the enhancement of image quality. This study attempts to examine that conclusion via the use of simple energy windowing technique. In the work reported here, data straddling the 81-154 keV range were segmented into three disjoints energy windows: photopeak, backscaterring, and angle-scattered regions. It is shown how image quality may be manipulated by appropriate combination of the sub-images derived from this data sets. Image were compared with those reconstructed from the data acquired within the conventional energy window (126-154 keV). It is found that the conventional view is the more correct one: scattered gamma-photons do, in general, reduce image quality . This conclusion is reinforced by the demonstration that some of the image enhancements claimed when scattered data is incorporated, may in fact be mimicked by processing the photopeak image alone.